Professional functions of social workers in Spain - Ballestero Izquierdo, Alberto; Viscarret Garro, Juan Jesús; Úriz Pemán, María Jesús (Cuadernos de Trabajo Social, 2013)
The results presented here are a part of a nationwide study which has surveyed, for the first time in Spain, female social workers registered in their official Associations in order to identify their daily practice, according to the classification of functions contained in the White Paper of Social Work. The results are presented in three sections: a) a description of general trends, b) a factor analysis for a typological grouping and classification of the functions of social workers and c) a cluster analysis aimed to group the social workers according to their functions into four main professional profiles, namely: management-planning, intervention for change, care intervention and academic. The results of the research point to the need to reflect on the future of the activity of female social workers in society and the academic orientation of the Degree in Social Work, since university education can meet the needs of a «labor market in the social field», with mainly an administrative and management character, or it may train the professionals to perform all of the functions that the reflective tradition of the discipline (research) and the historical evolution of the profession have set as essential to it (intervention).
Keywords: functions; profession; social work; social workers; Spain.